Exploring the perceptions and experiences of mobile teams on COVID-19 vaccine uptake at the community level: evidence from Benue and Niger states - Saheed Dipo Isiaka; Akolade Uthman Jimoh; Olugbemisola Wuraola Samuel; Sunday Atobatele; Sidney Sampson; Joshua Cinwonsoko David; Irene Okoye; Zubair Adegoke; Victor Daniel; Sunday Nto (BMC, 2024)
Abstract Background As part of the fight against coronavirus disease, Nigeria received nearly 4 million doses of the COVID-19 vaccine via the COVID-19 Vaccines Global Access (COVAX) Facility, marking a historic step towards equitable global distribution of COVID-19 vaccines. Although evidence exists on COVID-19 hesitancy in Nigeria, yet, we are unaware of any study on the optimization of COVID-19 vaccination from the lenses of the mobile teams. Objective This study seeks to explore the perceptions and experiences of mobile teams in selected communities during the implementation of COVID-19 vaccination in Benue and Niger. Methods An exploratory approach was adopted, and the study was conducted in Niger and Benue states based on poor performance in COVID-19 vaccination. Focus Group Discussions (FDGs) were conducted among 12 mobile vaccination teams from 12 LGAs. The recorded discussions were transcribed and coded (inductively and deductively) using Dedoose software (v9.0). Four themes and seven sub-themes were generated from the participants' responses. Results Seventy-two (72) health workers including vaccinators, validators, Electronic Management of Immunization Data (EMID) recorders, social mobilizers, and paper recorders participated in this study. Health workers' perceptions and experiences were thematized using the health building blocks. The mobilization teams in Benue and Niger states perceived that their mobilization efforts contributed to improved coverage, increased accessibility, and reduced hesitancy among the community dwellers. Challenges reported by the teams were vaccine misconceptions, requests for incentives in exchange for vaccine uptake, poor network services, distance to communities, and vaccine stockout. Conclusion This study concluded that social mobilizers play key roles in vaccine uptake, especially at the community level. Their roles in creating awareness, sensitization, and bringing the vaccine closer to hard-to-reach communities contributed to the success attained in the fight against COVID-19 in both states.